EXPLORING MATHEMATICAL COMMUNICATION SKILLS OF JUNIOR HIGH SCHOOL STUDENTS ON STATISTICS: A DESCRIPTIVE QUALITATIVE STUDY - Andari, Mayang Tri; Suardani, Ketut (Perpendicular : Journal of Mathematics Education and Learning, 2025)
The objective of this study was to analyze junior high school students’ mathematical communication skills on the topic of statistics. This research employed a descriptive qualitative approach. The subjects consisted of 30 students of class IX.A at SMP Negeri 1 Belitang III who were given a written mathematical communication test. Based on the test results, students’ abilities were classified into three levels: high, moderate, and low. Furthermore, three students representing each level were selected as main research subjects for in-depth analysis through interviews. Data were collected using tests, interviews, and documentation, and analyzed through scoring, classification, data reduction, presentation, and verification. The results showed that 20% of students had high mathematical communication skills, 33.3% were in the moderate category, and 46.6% were categorized as low. The main difficulties experienced by students were related to understanding written mathematical representations and restating mathematical ideas in their own words.